Sharpening of Plunge Shaving Cutters - 刘俐平; 李华敏 (Jixie chuandong)
The tooth curve of a plunge shaving cutter for an external gear is a recess transcendental curve,so it is difficult to grind it.This paper presents the method for sharpening flanks of the plunge shaving cutter by modifying a grinding wheel in a general grinding machine,optimizes the sharpening parameters and lays the foundation for the production and application of the plunge shaving cutter.